Public open space in the central business district of Cape Town - Daniels, Donald George (School of Architecture, Planning and Geomatics, 2016)
For the present, at least, the Central Business District of a City has the potential to provide opportunity, amenity and diversity for those people who care to seek it out. This would perhaps not be worthwhile or so interesting were it to lack the day to day and long-ranging problems that confront the individual, the household, the firm, the interest group, the pressure group and the planner in this unique environment. If the challenge is to be accepted then the environment should be questioned in order to find out if it will continue to exist and what structure and form it should have. Since the city centre is traditionally the pedestrian domain it is as well to study the space in which the pedestrian has to perform, before he is driven out of it, which hopefully might not be for some time to come. Little can be said in this thesis that has not been said before and the aim is here not concerned with networks, matrices or models nor can there be any detailed determinism of standards, actual physical elements or methods of affectuation. The attempt is an investigation of some aspects of the pattern of the open spaces and of the people who use them, and an attempt to gauge the extent of the regard for people in the open space network of the C.B.D. Because of the Republic's racial policy all places downtown are not for all the people all the time and in order to be significant this investigation would have to study the different social patterns for each race group, however the subject is treated as though the population were homogeneous. The street in the C.B.D., more than any other place anywhere else is for everyone.